Eksistensi Bahasa Bali Di Ranah Milenial (Studi Kasus Kemunculan Parodi Hai Puja) - Ni Nyoman Ayu Suciartini (Kamaya: Jurnal Ilmu Agama, 2018)
This research analyzes some parody videos of "Hai Puja" titled "Anak Kuliah Jaman Now", "Mantu Cager", "Happy Mother's Day, Memek", and "Celengan Out" which has been watched by thousands of people is a Bali-language video using Balinese language with a sense of comedy that is full of meaning and messages that fit the social context of contemporary society, especially in Bali. The use of the Balinese language in this video is a proof of the existence of the Balinese language in the Millenial era. The proof, this video audience is mostly a group of teenagers who enjoy it through uploading social media instagram, facebook, and youtube. Terms popularized in the language of Bali was much followed and discussed actively by the community, especially teenagers. Balinese language is a language that serves as a communication tool for the people of Bali, because the language of Bali is the mother tongue for the people of Bali. Balinese language is a reflection of all aspects of human life and also as a language of instruction in the social. Balinese language has a position and function that is able to become the identity and identity of Balinese people. As for some functions of the language of Bali is very important for the community, among others, as a symbol of pride of Bali, as a means of communication or liaison in the community, as the identity of the people of Bali.